Digitalization, financing constraints and firm performance - Kuang, Yiming; Fan, Min; Fan, Yaojun; Jiang, Yan; Bin, Jie (Frontiers in Environmental Science, 2023)
The development of low-level digital technology and communication technology such as “huge wisdom moving cloud” has driven the rise of digital economy, and various fields of social economy have gradually realized deep integration with digital technology. From the micro level of enterprises, digitalization transforms business activities such as research and development, production, supply chain and sales, and forms new data resources to help enterprises achieve lean management through data integration and analysis. To investigate whether digitalization ultimately affects firm performance, this study conducted theoretical discussions, selected Chinese listed companies to study, and empirically tested the relationship. Research has found that digitisation does boost corporate performance. After the robustness test, the conclusion remains the same. To deepen the understanding of the impact of digitalization on corporate performance, a mechanism analysis is also performed in this study. We found that digitization improves corporate performance by improving corporate innovation. In addition, we carried out an applicability analysis. We find that digitalization has a greater impact on firm performance in non-state-owned enterprises and those whose executives have an information technology background. Finally, by means of the economic consequences test, we find that the improvement in corporate performance caused by the growth of the digital hierarchy improves the corporate debt structure in the future. The findings of this study enrich theories related to digitalization and improve empirical evidence for the positive externalities of digitalization.